Analisa Stabilitas Lereng Dengan Menggunakan Software GeoStudio 2023 Pada Lereng Aliran Sungai Brantas di Wilayah Permukiman Wringinanom Gresik - Ardiansyah, Mohammad Raffael (Jurnal Vokasi Teknik Sipil, 2023)
People who live in Wringinanom Subdistrict live not too far from the presence of the Brantas River. Population growth around the slopes of the Brantas River causes many houses to be built around the slopes of the Brantas River in Wringinanom District. The construction of residential houses will affect the stability of slopes on the slopes of the Brantas River in Wringinanom District. This research was conducted to analyze the stability of slopes on the Brantas River using GeoStudio 2023 software. Soil parameter data used is data when soil conditions are 75% saturated or what is commonly called annual rainfall conditions. Based on the results of the analysis using GeoStudio 2023 software, a value of 1.187 was obtained, which according to the Bowles (1984) classification, the Brantas River slope in Wringinanom District is in critical condition or prone to landslides.